2023
DOI: 10.1039/d2nr05022f
|View full text |Cite
|
Sign up to set email alerts
|

Second-order nonlinear optical properties of copper-based hybrid organic–inorganic perovskites induced by chiral amines

Abstract: Recently, chiral hybrid organic-inorganic perovskites (HOIPs) are drawing wide attention due to their intrinsic noncentrosymmetric structures which result in fascinating properties such as ferroelectronics and second-order nonlinear optics (NLO). However,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…The results demonstrated the strong SHG signals in the NIR (840–1040 nm) range. The SHG peak’s location, which is peculiarly dependent on the pump wavelength intensity but always occurs at half of the pump wavelength, agrees with several chiral metal hybrid halides reports. The R -2-mpip­[SnBr 3 ]Br single crystal’s strongest SHG signal was recorded at 500 nm when the pump light was at 1000 nm. SHG signals related to the polarization angle were collected at intervals of 10° in order to study the impact of polarization on the SHG response.…”
Section: Resultssupporting
confidence: 88%
“…The results demonstrated the strong SHG signals in the NIR (840–1040 nm) range. The SHG peak’s location, which is peculiarly dependent on the pump wavelength intensity but always occurs at half of the pump wavelength, agrees with several chiral metal hybrid halides reports. The R -2-mpip­[SnBr 3 ]Br single crystal’s strongest SHG signal was recorded at 500 nm when the pump light was at 1000 nm. SHG signals related to the polarization angle were collected at intervals of 10° in order to study the impact of polarization on the SHG response.…”
Section: Resultssupporting
confidence: 88%
“…Li et al applied R-/S-NEA (NEA = 1-naphthylethylamine) and R-/S-CYHEA (CYHEA = 1-cyclohexylethylamine) as the A-site cation of CHP and synthesized CHP with circular dichroism. 80 Song et al applied R/S-MBA (MBA = alpha-methylbenzylaminium) as the A-site cation, giving the as-prepared CHP single crystals excellent circularly polarized luminescence. 81 (2) Pressure-induced PL enhancement: Li et al reported significant PL enhancement in CsCu 2 I 3 due to inter- and intratetrahedra distortion at high pressure (Fig.…”
Section: Manipulation Of Optical Propertiesmentioning
confidence: 99%
“…Additionally, nontoxic blocklike (R,S-NEA) 2 CuCl 4 and needle-like (R,S-CYHEA) 6 Cu 3 Cl 12 single crystals were synthesized in 2023, exhibiting chiral CD signals. 166 Fig. 18 Schematic illustration of spin polarized electron generation for circularly polarized luminescence in the core-shell nanocrystals.…”
Section: Chiral Optical Behaviorsmentioning
confidence: 99%
“…Additionally, nontoxic block-like ( R , S -NEA) 2 CuCl 4 and needle-like ( R , S -CYHEA) 6 Cu 3 Cl 12 single crystals were synthesized in 2023, exhibiting chiral CD signals. 166…”
Section: Chiral Properties Of Hybrid Organic Inorganic Perovskitesmentioning
confidence: 99%